2016
DOI: 10.1007/s11130-016-0551-8
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Ready-to-Eat Expanded Snack with High Nutritional and Antioxidant Value Produced from Whole Amarantin Transgenic Maize and Black Common Bean

Abstract: The snack foods market is currently demanding healthier products. A ready-to-eat expanded snack with high nutritional and antioxidant value was developed from a mixture (70:30) of whole amarantin transgenic maize (Zea mays L.) and black common bean (Phaseolus vulgaris L.) by optimizing the extrusion process. Extruder operation conditions were: feed moisture content (FMC, 15-25 %, wet basis), barrel temperature (BT, 120-170 °C), and screw speed (SS, 50-240). The desirability numeric method of the response surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 22 publications
1
42
0
6
Order By: Relevance
“…In contrast, a study conducted by Joshi et al [9] showed that corn extrudates made with an addition of 7.5% of spirulina were harder than those made of pure corn. Despite these inconsistencies, the hardness and breaking stress are perceptible to consumers and were generally negatively correlated with the expansion and cell structure of the product, independent of the feed moisture content [16, 17, 26]. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a study conducted by Joshi et al [9] showed that corn extrudates made with an addition of 7.5% of spirulina were harder than those made of pure corn. Despite these inconsistencies, the hardness and breaking stress are perceptible to consumers and were generally negatively correlated with the expansion and cell structure of the product, independent of the feed moisture content [16, 17, 26]. …”
Section: Resultsmentioning
confidence: 99%
“…Using optimal conditions for extrusion, these authors found an increase in total phenolic content (74%) and antioxidant activity evaluated as ORAC (18%) and ABTS (20%) in the extruded snack with respect to the unprocessed whole-grain mixture. In general, the increase in phenolics during the extrusion process could be due to the destruction of cell walls, the consequent release of phenolic compounds, and the Maillard reaction products quantified as phenolic compounds [106]. In another study, a significant decrease of total polyphenols and antioxidant activity was observed in a bean/corn mixture during extrusion.…”
Section: Phenolic Compounds (Phenolic Acids and Anthocyanins)mentioning
confidence: 95%
“…Other authors are using an optimized technique to obtain extruded products (cereals or mixture cereal/legume) with high nutritional quality and high antioxidant value. A ready-to-eat expanded snack with high nutritional and antioxidant value was developed from a mixture (70/30) of whole amaranthine, transgenic maize, and black beans by optimizing the extrusion process [106]. Using optimal conditions for extrusion, these authors found an increase in total phenolic content (74%) and antioxidant activity evaluated as ORAC (18%) and ABTS (20%) in the extruded snack with respect to the unprocessed whole-grain mixture.…”
Section: Phenolic Compounds (Phenolic Acids and Anthocyanins)mentioning
confidence: 99%
“…The best processing conditions, able to ensure high expansion ratio, were 15% moisture and 238 rpm. A single-screw extruder was used [27]. The effect of the same parameters, feed moisture content and screw speed (in the ranges 14-18% and 400-550 rpm, respectively), was studied also during the production of rice-based extruded snacks containing 30% mung bean flour.…”
Section: Optimizing the Processing Conditions For Legume-added Extrudmentioning
confidence: 99%